Shift work, sleep, and burnout: the impact of Mediterranean dietary pattern and nutritional status on emergency healthcare workers - BAKIRHAN, YUNUS EMRE (My University, 2023)
Purpose This study aims to evaluate the relationship between dietary patterns and shift work, sleep quality and burnout among emergency health-care workers. Design/methodology/approach The nutritional status, sleep quality and burnout status of health-care workers (n = 91) in Turkey were investigated. Findings Among the burnout subgroups, only emotional exhaustion was associated with high adherence to the Meditarrenean diet. (r = 0.37, p < 0.01). Carbohydrates consumed during the shift day were associated with lower sleep quality (r = 0.24, p = 0.02). The intake of protein (r = -0.29, p < 0.01), fat (r = -0.27, p < 0.00), cholesterol (r = -0.31, p < 0.01), phosphorus (r = -0.22, p = 0.03) and iron (r = -0.21, p = 0.04) in shift day was negatively associated with Pittsburgh Sleep Quality Index (PSQI) scores (lower PSQI scores indicates good sleep quality). Consumption of vitamin C and potassium on the rest day was significantly associated with better sleep quality (respectively, r = -0.21, p = 0.04 and r=-0.23, p = 0.03). Personal accomplishment was positively correlated with carbohydrate consumption during the shift day and negatively correlated with protein, cholesterol and vitamin B6 intake (respectively, r = 0.22, p = 0.03; r = -0.21, p = 0.03; r=-0.28, p < 0.00, r = -0.28, p < 0.00). Emotional exhaustion was negatively correlated with protein consumption on the shift day (r = -0.21, p = 0.04) and positively correlated with fat consumption on the rest day (r = 0.22, p = 0.02). Originality/value The findings confirm the possible role of dietary patterns in health-care workers against burnout and sleep quality attributable to a possible association with nutrients intake on shift or rest day.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Yemek bilimi; Yaşam Bilimleri; Food Science; Life Sciences; Burnout; Health workers; Shift; Sleep quality; Dietary patterns; PHYSICAL-ACTIVITY; QUALITY; INDEX; Burnout; Health workers; Shift; Sleep quality; Dietary patterns